2005
DOI: 10.1086/497168
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal Secretions Contribute to Innate Resistance to Herpes Simplex Virus Infection

Abstract: Defining and preserving the innate antiviral activity found in cervicovaginal secretions is critical. Cervicovaginal lavage (CVL) samples were obtained from 20 healthy women and evaluated for anti-herpes simplex virus (HSV) activity. CVL samples reduced HSV-2 yields by 23-fold (median), and the anti-HSV activity of CVL samples correlated with the concentration of human neutrophil peptides (HNP)-1-3. Both CVL samples and HNP-1-3 interacted with virus and prevented entry after binding. Substantially less protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 19 publications
8
78
1
1
Order By: Relevance
“…First, we previously demonstrated that recombinant SLPI interacts with human epithelial cells to inhibit HSV infection in vitro (25). Downregulation could overcome the antiviral activity of SLPI in mucosal secretions, thus providing a mechanism for immune evasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we previously demonstrated that recombinant SLPI interacts with human epithelial cells to inhibit HSV infection in vitro (25). Downregulation could overcome the antiviral activity of SLPI in mucosal secretions, thus providing a mechanism for immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Cervicovaginal secretions provide intrinsic protection and inhibit HSV infection in vitro by as much as 90% (25,27). Multiple factors may contribute to this activity, including the acidic pH of the healthy female genital tract and antimicrobial proteins such as mucins, defensins, lactoferrin, lysozyme, and secretory leukocyte protease inhibitor (SLPI) (21,32,47).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, John et al have tested cervico-vaginal lavage (CVL) from healthy women and found that they have an intrinsic ability to inhibit HSV-2. Anti-HSV-2 activity correlated with the concentrations of α-defensins in CVL [207]. CVL has also been shown to contain antimicrobials SLPI, lactoferrin and gp340 that are inhibitory to HIV replication in vitro and therefore might potentially inhibit viral entry in vivo [209].…”
Section: Secretory Microbicidesmentioning
confidence: 99%
“…In addition, the envelope glycoprotein gp120 from X4/T-Tropic HIV-1 induces the mRNA expression of HBD2, SLPI, and IL-8 by uterine and Fallopian tube epithelial cells (Ghosh et al, unpublished observations). Several of the antimicrobials described above are effective in killing gram-positive and gramnegative bacteria, fungi, and viruses including N. gonorrhoeae, C. trachomatis, C. albicans, herpes simplex virus-2 (HSV-2), and HIV-1, all of which are important reproductive tract pathogens [202,[204][205][206][207]. Other factors found in FRT secretions exhibiting antiviral activity, notably against HIV-1, are the chemokines MIP-1α, MIP-1β, regulated upon activation, normal T-cell expressed and secreted (RANTES), and stromal derived factor 1 alpha (SDF-1α) which inhibit HIV-1 infection of target host cells by interfering with the ability of HIV-1 to bind coreceptors CCR5 and CXCR4 found on host cells [208].…”
Section: Secretory Microbicidesmentioning
confidence: 99%